Learning to Live Together: How Does Multicultural Education Build Religious Tolerance in Fakfak, West Papua? - Qodriyah, Khodijatul; Asfiyah, Hilmatul; Rozi, Fathor (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2025)
The multireligious community life in Fakfak, West Papua, is an important reflection of how local cultural values ​​can support religious tolerance in everyday life. This study aims to examine how multicultural education shapes and strengthens religious tolerance in Otoweri Village, Tomage District, Fakfak Regency. The method used was a qualitative approach with a case study through interviews, observation, and documentation. The research results show that community involvement in interfaith activities such as mutual cooperation, community discussions, and joint celebrations of religious holidays demonstrates a strong collective awareness of maintaining harmony. Children are also actively involved in interfaith interactions through games and group learning activities, demonstrating that the value of tolerance is instilled from an early age. The local cultural concept of